(3GdeYhfGJ hGdefM GdOhdjI hGKQgG Ydi GdJfejI GdTGedI aj GdhWf GdYQHj (B/s ((3GdbGgQI(B: s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2007)
(3GdGJGgGJ GdMOjKI aj GOGQI eYhfGJ GdJfejI GdQSejI eY HOGjI GdCdajI GdLOjOI, JbOjQ GdMLe GdCeKd ddefM hGdeYhfGJ GdNGQLjI ddGbJUGO Gdbhej HGdJWHjb Ydi eedcI GdHMQjf, JLQHI Gdjef aj GdGUdGMGJ GdGbJUGOjI hGKQgG Ydi Gdfeh GdGbJUGOj, GdefM hGdeSGYOGJ GdOhdjI hCKQgG Ydi GdJfejI GdGbJUGOjI aj GdGQOf, GdeYhfGJ hGdJfejI GdGbJUGOjI MGdI JWHjbjI Ydi GdGbJUGO GdGQOfj, GdeYhfGJ GdOhdjI hYdGbJgG HGdJfejI adSWjf fehPLG, fehPL JNWjW hGOGQI eTQhYGJ GdgjFGJ GdOhdjI GdeGfMI dJfejI GdeOf GdMVQjI, GdeaGgje hGdeeGQSGJ GdJfehjI ddgjFI GdYQHjI ddGSJKeGQ hGdGfeGA GdRQGYj, JLQHI TQcI VeGf eNGWQ GdGFJeGf GdeUQjI, (BSTRUCTURAL ADJUSTEMENT PROGRAMS: EVIDENCE FROM THE RECENT EXPERIENCE OF HORDAN(3, LghO GdHfc GdOhdj aj GdJfejI hGdJYGhf eY LeghQjI eUQ GdYQHjI, (BTHE ROLE OF TECHNICAL ASSISTANCE IN ECONOMIC DEVELOPEMENT (3, (BTHE ROLE OF USAID IN WATER SECTOR REFORM : A CASE STUDY (3,eTQhY eeQ YeGf GdJfehj GdeTQhY hGdJehjds
(3HHdjhZQGajG(B: (3U(B.249-251s
Keywords: (3GdCbdjGJs; (3GdJfejI GdGbJUGOjIs; (3GdeYhfI GdEbJUGOjIs